Vegetation of the Arabian Peninsula Geobotany 25 - Fisher, Martin; Ghazanfar, Shahina A. (Kluwer Academic Publishers, Dordrecht, 1998)
Vegetation of the Arabian Peninsula is the first comprehensive book on all aspects of the vegetation, phytogeography and conservation of the vast and varied region of the Arabian Peninsula. Written and edited by experts on the botany and environment of the Peninsula, this book synthesises the information available on all aspects of the flora and vegetation (including lower plants), from the mountains, sand seas, coasts, water bodies and desert plains to the plants of economic importance. The book contains chapters on the vegetation, ecology and phytogeography of the mountains, wadis, sand deserts, gravel plains, coasts and sabkhas. Chapters on climate and geology provide the background information for understanding the dynamics of the vegetation. A chapter on the diversity of plants gives details of the region's species richness and endemism, current threats to plant diversity and the measures taken in the form of protected areas and legislation in each country of the Peninsula. An invaluable reference for Southwest Asian botany.
English
Keywords: S 1-(972) Agriculture (General); Southwest Asia